Novel Research Aspects in Mathematical and Computer Science Vol. 4 - Ferreira, M. A. M. (2022)
This book covers key areas of Mathematical and Computer Science. The contributions by the authors include field theory, homogeneous equations, Roofline model, multicore CPU, parallel work, Quantum perspective model, danio kyathit, danio aesculapii, square roots, Natural (free) convection, viscous incompressible, skin friction, nusselt number, sherwood number, chemical reaction, soret number, couette flow , Symmetric matrix, differential equations, Eigen values, Eigen vectors, modal matrix, spectral matrix, Twin edge coloring, twin chromatic index, splitting graph, middle graph, shadow graph, Tripolar fuzzy set, Bi-ideal, Weak bi-ideal, Tripolar fuzzy ideal, Tripolar fuzzy weak bi-ideal of a near ring, tripolar fuzzy ideal of a near algebra, J-closed function, J-closed set, J-open set, J-open function and ?^*-open sets, Dihedral group, semi-simple group algebra, minimal idempotent, central idempotent, orthogonal idempotent, simple component, Wedderburn decomposition, Information-measuring systems, digital signal processing, discrete averaging, Fuzzy closure space, fuzzy biclosure space, Nonband-limited function, derivative interpolation, ill-posedness, and regularization. This book contains various materials suitable for students, researchers and academicians in the field of Mathematical and Computer Science.